Pengaruh Model Problem Based Learning terhadap Kemampuan Berpikir Kritis Matematis Siswa SMP - Fannisa Rahmadani; Sudianto Manullang (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The aim of this research is to find out whether there is an influence of the PBL model on students' mathematical critical thinking abilities in class VIII students at MTsN 2 Medan for the 2023/2024 academic year, by seeing whether the mathematical critical thinking abilities of students who are guided by the PBL model are higher than students' mathematical critical thinking abilities. who are guided through conventional learning models in the topic of flat-sided geometric figures (cubes and blocks). This research uses a type of quasi-experimental research. The sample for this research was class VIII-2 with 30 students as the experimental class taught using the PBL model and class VIII-3 with 30 students taught using the conventional model. The test instrument uses pre-test and post-test questions in the form of descriptions of 4 questions which are aligned with indicators of mathematical critical thinking abilities and have been validated. Before testing the hypothesis, a data normality test was first carried out using the Liliefors test and a data homogeneity test using the F test. After being given treatment, the PBL class obtained an average value of 90.42 and the conventional class obtained an average value of 79.82. From the results of one party t-test calculations, the results of the hypothesis test t-count > t-table are 4.5875 > 1.672, so it can be concluded that H0 is rejected or Ha is accepted. Thus, there is an influence of the PBL model on students' critical thinking abilities, where the critical mathematical thinking abilities of students taught using the PBL model are higher than the critical mathematical thinking of students taught using conventional learning models on flat-sided geometric material (cubes and blocks) in class VIII MTsN 2 Medan Academic Year 2023/2024.